2012
DOI: 10.2174/092986712800167356
|View full text |Cite
|
Sign up to set email alerts
|

Privileged Structures - Dream or Reality: Preferential Organization of Azanaphthalene Scaffold

Abstract: The concept of privileged structures/substructures (PS) is the idea that certain structural features produce biological effects more often than others. The PS method can be seen as an offspring of fragonomics, which is based on recent experimental measurements of protein-ligand interactions. If PS prove to be true, then chemical motives that enrich biological activity can be used when designing new drugs. However, PS remain controversial because we cannot be sure whether the excess of active structures does no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(24 citation statements)
references
References 279 publications
(343 reference statements)
1
23
0
Order By: Relevance
“…The results were, however, unexpected and lead to some interesting remarks. The compounds that were used in this study were obtained during our search for active styrylquinolines as published recently [ 2 , 7 , 28 – 33 ]. As this experiment was concentrated on the styryl part of the molecule, we modified it according to the idea that is depicted in Fig 2 .…”
Section: Resultsmentioning
confidence: 99%
“…The results were, however, unexpected and lead to some interesting remarks. The compounds that were used in this study were obtained during our search for active styrylquinolines as published recently [ 2 , 7 , 28 – 33 ]. As this experiment was concentrated on the styryl part of the molecule, we modified it according to the idea that is depicted in Fig 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Many of these frameworks have been used as templates for the design of libraries of molecules for drug discovery [130][131][132][133][134] . In fact, the privileged structure concept has emerged as a successful approach for the drug discovery process, e.g.…”
Section: Chromone As a Privileged Scaffold 251 Privileged Structurementioning
confidence: 99%
“…In fact, the privileged structure concept has emerged as a successful approach for the drug discovery process, e.g. as core structures for synthesis and optimal starting points for the library design of ligands with affinity to certain molecular targets [130][131][132][133][134] . The last decade has brought more popularity to this idea and numerous scaffolds have been claimed to be privileged:…”
Section: Chromone As a Privileged Scaffold 251 Privileged Structurementioning
confidence: 99%
“…Studying the azanaphthalene scaffolds from nature (e.g., quinolones and isoquinolines) one is struck by the number of bioactive compounds, both drugs and candidates as shown in the recent review by Polanski et al 4 Interestingly, this chapter does not discuss topological mimics of natural product structures such as ATP. Although bis-azanaphalene structures are discussed and some of the compounds currently under clinical trials as potential kinase inhibitors are shown, the concept of an NP-mimic is not addressed.…”
Section: A Selection Of Other Privileged Structural Classesmentioning
confidence: 99%